Liquoid Induced Stasis and the Generalized Shwartzman Reaction - Nordstoga, Knut (Thrombosis and Haemostasis, 1979)
The composition of the occlusive material within dilated glomerular capillaries, following intravenous injections of Liquoid in blue foxes, was studied electron microscopically; it was found that it mainly consisted of a debris in which disintegrated red cells constituted the major component. Damaged platelets and necrotic endothelial remnants were other components. These observations were interpreted as a result of glomerular stasis, and it was concluded that stasis in glomerular capillaries is a basic event in the development of the renal lesions accompanying the generalized Shwartzman reaction.